2019
DOI: 10.1073/pnas.1820585116
|View full text |Cite
|
Sign up to set email alerts
|

α-Sheet secondary structure in amyloid β-peptide drives aggregation and toxicity in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is characterized by the deposition of β-sheet–rich, insoluble amyloid β-peptide (Aβ) plaques; however, plaque burden is not correlated with cognitive impairment in AD patients; instead, it is correlated with the presence of toxic soluble oligomers. Here, we show, by a variety of different techniques, that these Aβ oligomers adopt a nonstandard secondary structure, termed “α-sheet.” These oligomers form in the lag phase of aggregation, when Aβ-associated cytotoxicity peaks, en route to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
214
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(231 citation statements)
references
References 56 publications
15
214
0
2
Order By: Relevance
“…This structure is highly similar to the β-sheet, except that the carbonyl oxygen atoms are aligned on one face of a strand and the NH groups on the other, instead of alternating with each other, giving rise to different physical properties to the protein. This structure was found in the early stages of the Aβ-peptide [ 38 , 39 ] and the transthyretin protein (TTR) aggregation [ 40 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…This structure is highly similar to the β-sheet, except that the carbonyl oxygen atoms are aligned on one face of a strand and the NH groups on the other, instead of alternating with each other, giving rise to different physical properties to the protein. This structure was found in the early stages of the Aβ-peptide [ 38 , 39 ] and the transthyretin protein (TTR) aggregation [ 40 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…Biophysical studies of the designed peptides support the presence of α-sheet, in addition to an NMR structure of one of the designs, 40 and the peptides successfully inhibit aggregation of TTR, β-amyloid peptide, islet amyloid polypeptide, 37,38,40 and amyloid-forming bacterial proteins from S. aureus 39 and E. coli, (Bleem et al, unpublished) as well as in the live bacteria 39,79 (Bleem et al, unpublished) by preferentially binding the toxic species over the nontoxic species of those unrelated peptides and proteins. Furthermore, we have confirmed that these amyloidogenic peptides and proteins form α-sheet during aggregation by CD, Fourier transform infrared (FTIR), and solution IR [37][38][39][40] (Bleem et al, unpublished). Also, independently, the FTIR peaks we have identified as signatures for α-sheet [37][38][39] have been observed by others in a fragment of TTR in the region of the structure predicted in our MD simulations.…”
Section: α-Sheet May Play a Role In P53 Aggregationmentioning
confidence: 84%
“…We hoped to also gain some insight into some of the peculiar properties of anti-amyloid antibodies, such as why many of them are specific for aggregates, why they recognize generic epitopes that do not depend on a specific amino acid sequence and why the A11 and OC series antibodies recognize mutually exclusive aggregation-specific epitopes. A11 binds known repeating antiparallel beta structures, such as antiparallel Aß42 prefibrillar oligomers (26), hemolysin pores (14) and beta cylindrins (27) and antibodies in A11 serum also bind to -sheet structures (28). OC binds to known parallel, inregister structures, such as Aß (12), -synuclein and IAPP fibrils (7).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six of the monoclonals clearly recognize an Aß related epitope that is located in the aminoterminal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) or central (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) thirds of the molecule or both (Fig. 1).…”
Section: Epitomic Analysis Of Monoclonal Antibody Specificitymentioning
confidence: 99%